Evolution, Clinical and Microbiological Characteristics of Invasive Pneumococcal Disease since the Introduction of the Pneumococcal Conjugate Vaccine 13-Valent in Adults over 18 Years Old - Juan Buades (Vaccines, 2021)
Invasive pneumococcal disease (IPD) presents high mortality in the population at risk. The aim of this work is to know the evolution, clinical and microbiological characteristics of IPD in the adult population of Majorca, since the introduction of a public funded program for pneumococcal conjugate vaccine (PCV-13) in the pediatric population in the Balearic Islands in 2016. For this purpose, a retrospective multicenter study was carried out in which all episodes of IPD in adult patients from the four hospitals of the public health system of Majorca were included, comparing the periods between 2012 and 2015 and between 2016 and 2019. Clinical variables, serotypes and antibiotic sensitivity were collected. There were 498 cases of IPD; 56.8% were male with a mean age of 67 (standard deviation: 16). Most infections were bacterial pneumonias (73.7%). Of the total cases, 264 (53%) presented complications. Of the 498 cases, 351 strains were obtained, of which 145 (41.3%) belong to vaccinal serotypes (included in the PCV-13 vaccine) and 206 (58.7%) to non-vaccinal serotypes (not included in the PCV-13 vaccine). The percentage of IPD caused by vaccinal serotypes was lower in the second period (47.8% vs. 34.5%; p = 0.012).